Efektivitas Pelaksanaan Program Pengelolaan Sampah Berbasis Sumber - I Made Dicky Taruna Wijaya; Ida Ayu Putu Widiati; I Wayan Arthanaya (Fakultas Hukum Universitas Warmadewa, 2022)
The implementation of source-based waste management as stipulated in the Bali Governor Regulation Number 47 of 2019 is one solution in handling waste in Denpasar City. It is necessary to conduct a special study on the effectiveness of source-based waste management implemented in Denpasar City. Based on this background, the following problems can be formulated: 1) What is the arrangement for waste management in Denpasar City? 2) How is the effectiveness of source-based waste management in Padangsambian Village? This type of research in scientific writing is empirical legal research. The results show that the effectiveness of source-based waste management in Padangsambian Village is still not maximized due to population growth factors that have an impact on increasing the volume of waste every year caused by the increase in population, the quality and quantity of Human Resources (HR) which are still inadequate and operational technicalities. , there are still obstacles in management with the lack of budget in the village.